FAKTOR KEMAJUAN TEKNOLOGI DAN SUMBER DAYA MANUSIA TERHADAP PENINGKATAN PENDAPATAN UMKM ERA REVOLUSI 4.0 - Achmad Nur Fuad Chalimi; Siti Herdinawati; Asadi Asadi (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2021)
This study was to analyzed technological advances and human resource capabilities factors to increase income in the Industrial Revolution Era during the Covic-19 Pandemic especially in Pasuruan Regency, using quantitative research with questionnaires. The data was analyzed using multiple regression with SPSS analysis tools. The result showed that in this current era of the industrial revolution 4.0, technology was very helpful in the business world, whether it’s micro, small or even medium scale, getting a positive impact. Everything can be accessed, especially in product marketing. The need for involvement of both business owners and employees who work must be able to understand and be directly involved in the use of the technology. Through the use of the marketplace, MSMEs' income has increased. Human resources must have unique knowledge, skills and even motivation to develop a business so that the desired amount of income can be achieved. Human resources are an important factor that must be considered in achieving the company's target goals, namely income that is always increasing so that it can maintain business continuity. The use of technological advances and human resource capabilities affect MSME income in Pasuruan Regency.